2015
DOI: 10.21157/j.med.vet..v9i2.3983
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN KACANG PANJANG (Vigna unguiculata) TERHADAP KADAR GLUKOSA DARAH MENCIT (Mus musculus) YANG DIINDUKSI ALOKSAN (Effect of Long Bean (Vigna unguiculata) on Blood Glucose Level of Mice (Mus musculus) Induced by Alloxan)

Abstract: ABSTRAKPenelitian ini bertujuan mengetahui pengaruh pemberian kacang panjang (Vigna unguiculata) terhadap kadar glukosa darah mencit (Mus musculus) yang diinduksi aloksan. Dalam penelitian ini digunakan 12 ekor mencit dengan berat 25-40 g yang secara klinis dinyatakan sehat. Mencit dibagi menjadi empat kelompok perlakuan, masing-masing kelompok perlakuan terdiri atas tiga ekor mencit. Kelompok K0 adalah kelompok kontrol negatif, hanya diberi akuades. Kelompok K1, K2, dan K3 adalah kelompok yang diinduksi aloks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
2
0
1
Order By: Relevance
“…Group positive control (K+) alloxan induced had the largest diameter; this is in line with research by Fanhriyansyah (2021), which stated that alloxan induced in mice will result in hyperglycemia, which furthermore will result in hypertrophy of the glomerulus because there is pressure on the glomerular cells [15]. Research done by Handani showed that mice induced with alloxan would have a widening glomerulus This results in adhesions between the glomerulus and Bowman's capsule [16]. Meanwhile, in the treatment group, the average flat on group P1 was 53,53 μm, group P2 was 53,28 m, and group P35 was 2.20 μm.…”
Section: Iii1 Discussionsupporting
confidence: 80%
“…Group positive control (K+) alloxan induced had the largest diameter; this is in line with research by Fanhriyansyah (2021), which stated that alloxan induced in mice will result in hyperglycemia, which furthermore will result in hypertrophy of the glomerulus because there is pressure on the glomerular cells [15]. Research done by Handani showed that mice induced with alloxan would have a widening glomerulus This results in adhesions between the glomerulus and Bowman's capsule [16]. Meanwhile, in the treatment group, the average flat on group P1 was 53,53 μm, group P2 was 53,28 m, and group P35 was 2.20 μm.…”
Section: Iii1 Discussionsupporting
confidence: 80%
“…Alkaloids act as antidiabetic, both in extracts and isolated molecules. It inhibited the glucosidase enzyme, deactivated DPP-IV (Dipeptidyl Peptidase-4), improved insulin sensitivity, and reduced oxidative stress (Ajebli et al 2021) Vitamin C helps repair damaged cells and insulin resistance and inflexible blood vessels associated with diabetes (Aprila et al 2015). Vitamin C is a group of micronutrients that plays a role as an antioxidant in human plasma and functions as an electron donor or electron reducing agent, which allows it to serve as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…According to Maha (2013), Vitamin C can lower fasting blood glucose, which can provide primary and secondary protection against oxidative damage to lipids and lipoproteins and improve the negative effects of DM. Aprila et al (2015) stated that magnesium simplifies glucose transport into cells, cofactors various enzymes involved in the glucose oxidation process, and helps to increase insulin sensitivity and avoids insulin resistance (Larsson and Wolk 2007). In addition, intracellular magnesium deficiency can reduce the action of tyrosine kinase on insulin receptors (Mulatsih 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Radikal bebas akan mencapai kestabilan atom atau molekul dengan cara bereaksi dengan molekul di sekitarnya untuk memperoleh pasangan elektron. Reaksi ini akan terus berlangsung dan bila tidak dihentikan akan menimbulkan berbagai penyakit degeneratif seperti diabetes mellitus (Aprilia et al, 2015).…”
Section: Pembahasanunclassified